It Gave Me Somebody Else to Think About Besides Myself: Caring Callers Volunteer Experiences With a Telephone-Based Reassurance Program for Socially Isolated Older Adults. (January 2023) - Fields, Noelle L.; Lee, Kathy; Cassidy, Jessica; Kunz-Lomelin, Alan; Stringfellow, Mary K.; Feinhals, Gretchen
The Caring Callers Program was developed as a telephone-based intervention utilizing Senior Companion volunteers to reach older adults at greater risk for loneliness during the COVID-19 pandemic. This pilot program consisted of trained volunteers who provided supportive, weekly calls as well as community resources with their Caring Callers clients. The purpose of this study was to qualitatively explore the experiences of Senior Companion volunteers in the Caring Callers Program through the lens of productive aging. We completed semi-structured interviews with 18 Caring Callers volunteers. We used Rapid and Rigorous Qualitative Date Analysis (RADaR) which yielded four themes: (1) reciprocity; (2) purposeful use of time; (3) learning new skills; and (4) gaining perspective. Our findings provide insight for gerontological researchers examining volunteering as a productive aging activity and offer strategies for designing peer-led, telephone-based interventions to promote social connectedness in an unprecedented time.